A coupled meshless finite point/Peridynamic method for 2D dynamic fracture analysis. (December 2016) - Shojaei, A.; Mudric, T.; Zaccariotto, M.; Galvanetto, U.
Abstract: In this paper, a new coupled meshless method for 2D transient elastodynamic problems involving dynamic crack propagation is developed. The method is based on an efficient coupling between the finite point method (FPM) and a discretized form of Peridynamics. The solution domain is partitioned in three parts: one discretized by Peridynamics, one by FPM, and a transition part discretized by both methods where the switching between the two approaches is performed. The coupling adopts a local/nonlocal framework that benefits from the full advantages of both methods. The parts of domain where cracks either exist or are likely to propagate are described by Peridynamics; the remaining part of the domain is described by FPM that requires less computational effort. The capabilities of the proposed approach are demonstrated by means of the solution of dynamic problems including dynamic fracture as well as a ghost force test. Highlights: A new coupled meshless method for elastodynamic problems as well as problems involving crack propagation is developed. The proposed method is based on a suitable coupling between the meshless Finite Point method and a meshless Peridynamic method. The coupling is done in a simple manner without introducing extra numerical artifacts. The coupling technique is free of the presence of ghost forces. The coupled method produces the solution of a Peridynamic-only model by using a much smaller number of nodes.